Kontribusi Kepemimpinan Transformasional, Motivasi Kerja, Etos Kerja, dan Iklim Kerja Terhadap Kinerja Guru di SD Negeri Gugus 3 Kecamatan Kuta Utara Kabupaten Badung - Yunitasari, Made Ayu Mas; Agung, A.A.G; Yudana, I.M (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to (1) describe the magnitude of the contribution of transformational leadership to teacher performance at SD Negeri Gugus 3, North Kuta District, Badung Regency, (2) describe the magnitude of the contribution of work motivation to teacher performance at SD Negeri Gugus 3, North Kuta District, Badung Regency, (3) describe the magnitude of the contribution of work ethic to teacher performance at SD Negeri Gugus 3, North Kuta District, Badung Regency, (4) describe the magnitude of the contribution of work climate to teacher performance at SD Negeri Gugus 3, North Kuta District, Badung Regency, (5) determine the magnitude of the contribution of transformational leadership, work motivation, work ethic, and work climate together to teacher performance at SD Negeri Gugus 3, North Kuta District, Badung Regency. This study is an "ex-post facto" study with a sample size of 103 people, taken using the proportional random sampling technique from a population of 138 teachers. Data were collected using a questionnaire. Data analysis was carried out using the product moment correlation technique, multiple regression, and partial correlation. The results of the study show that: (1) there is a positive and significant contribution of transformational leadership to teacher performance at SD Negeri Gugus 3, North Kuta District with a correlation coefficient of 0.705 and an effective contribution of 22.56%, (2) there is a positive and significant contribution of work motivation to teacher performance at SD Negeri Gugus 3, North Kuta District with a correlation coefficient of 0.609 and an effective contribution of 13.34%, (3) there is a positive and significant contribution of work ethic to teacher performance at SD Negeri Gugus 3, North Kuta District with a correlation coefficient of 0.714 and an effective contribution of 19.71%, (4) there is a positive and significant contribution of work climate to teacher performance at SD Negeri Gugus 3, North Kuta District with a correlation coefficient of 0.677 and an effective contribution of 16.86%, (5) there is a positive and significant contribution together of transformational leadership, work motivation, work ethic and work climate to teacher performance at SD Negeri Gugus 3, North Kuta District with a correlation coefficient of 0.677 and an effective contribution of 16.86%, (6) there is a positive and significant contribution together of transformational leadership, work motivation, work ethic and work climate to teacher performance at SD Negeri Gugus 3, North Kuta District with a correlation coefficient of 0.677 and an effective contribution of 16.86%, (7) there is a positive and significant contribution together of transformational leadership, work motivation, work ethic and work climate to teacher performance at SD Negeri Gugus 3, North Kuta District with a correlation coefficient of 0.677 and an effective contribution of 16.86%, (8) there is a positive and significant contribution together of transformational leadership, work motivation, work ethic and work climate to teacher performance at SD Negeri Gugus 3, North Kuta District with a correlation coefficient of 0.677 and an effective contribution of 16.86%, (9) there is a positive and significant contribution together of transformational leadership, work motivation, work ethic and work climate to teacher performance at SD Negeri correlation of 0.817 and contribution of = 72.46%.